Implementation of telenursing in the Slovak Republic - Kristová, Jarmila; Bachratá, Zuzana; Slezáková, Zuzana; Miklovičová, Emília (Nursing in the 21st Century, 2021)
IMPLEMENTATION OF TELENURSING IN THE SLOVAK REPUBLIC Aim. The aim of this study was to show on the example of good practice the possibilities of implementing telenursing in the nursing fields of neonatology and pediatrics. The new nursing approach was implemented by creating a website www.telesestra.sk. Such online counseling, consultancy and education, which was focused on the care for newborns and infants, were provided for six months. Material and method. A method called content and quantitative analysis of text/document was chosen to fulfill the goal. In our case, the content and quantitative analysis was realized on the electronic document – a website, whose central part was comprised of the online counseling and professional articles with educational content primarily intended for mothers with children. Results. The number of 2914 visitors showed interest in the website. As many as 36 questions were registered, which mainly focused on the issues with breastfeeding and care for newborns and infants. Conclusions. Based on the example of good practice, the development of telenursing can also be supported in other fields, as well as drawing attention to education and training of nurses in the field of information and communication technologies and exchanging work experience with nurses from those countries, where telenursing is already an integral part of the health care system.